Health and Poverty in Guatemala - Gragnolati, Michele; Marini, Alessandra (World Bank, Washington, DC, 2014)
Unlike many other countries in Latin America, Guatemala is only at the beginning of the demographic, and epidemiological transition. The population is young, is growing rapidly, and is still primarily rural. Guatemala is among the worst performers in terms of health outcomes in Latin America, with one of the highest infant mortality rates, and one of the lowest life expectancies at birth. Major causes of death in Guatemala still include treatable, and communicable diseases, such as diarrhea, pneumonia, cholera, malnutrition, and tuberculosis. A significant share of Guatemalans lack access to health care services. A combination of both supply- and demand-side constraints limit the ability of households to seek health care services in Guatemala, with supply-side constraints playing a more dominant role in rural areas than urban. Some progress has been made in reforming the health sector. Important steps have been taken on the institutional side, with health being one of the pilot ministries to decentralize financial management under the Integrated System for Health Care (SIAS program). Public spending has shifted toward preventive care, which is essential for treating the health problems faced by the poor. Despite these efforts, spending and health outcomes has not improved significantly. In addition, public spending on health is not well targeted. Overall, public health spending benefits the highest quintiles disproportionately, By type of facility, public spending on hospitals is by far the more regressive.